2020
DOI: 10.1002/chem.201905605
|View full text |Cite
|
Sign up to set email alerts
|

Distance Matters: Effect of the Spacer Length on the Photophysical Properties of Multimodular Perylenediimide–Silicon Phthalocyanine–Fullerene Triads

Abstract: A multimodular donor–acceptor conjugate featuring silicon phthalocyanine (SiPc) as the electron donor, and two electron acceptors, namely tetrachloroperylenediimide (PDI) and C60, placed at the opposite ends of the SiPc axial positions, was newly designed and synthesized, and the results were compared to the earlier reported PDI‐SiPc‐C60 triad. Minimal intramolecular interactions between the entities was observed. Absorption, fluorescence, computational and electrochemical studies were performed to evaluate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 80 publications
(48 reference statements)
0
9
0
Order By: Relevance
“…The PDI peaks were located at 498 and 532 nm, and revealed about 2 nm red‐shift going from toluene (dielectric constant, ϵ=2.38) to N , N ‐dimethylformamide (DMF, ϵ=37.7). These spectral features were typical of PDI monomer [9] without any spectral broadening suggesting lack of ground state interactions between the PDI entities of the dimer. [10] Another broad peak at ∼350 nm range was observed and was attributed to the azobenzene entity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PDI peaks were located at 498 and 532 nm, and revealed about 2 nm red‐shift going from toluene (dielectric constant, ϵ=2.38) to N , N ‐dimethylformamide (DMF, ϵ=37.7). These spectral features were typical of PDI monomer [9] without any spectral broadening suggesting lack of ground state interactions between the PDI entities of the dimer. [10] Another broad peak at ∼350 nm range was observed and was attributed to the azobenzene entity.…”
Section: Resultsmentioning
confidence: 99%
“…Although known to be inefficient for the earlier mentioned reasons, the 1 PDI* could populate the 3 PDI* ( E T =1.07 eV) [9] via an intersystem crossing process, hence, efforts were also made to spectrally characterize 3 PDI*‐control 1 using nanosecond transient absorption (ns‐TA) spectroscopy. Direct excitation of PDI‐control 1 gave no measurable signal, hence, 3 PDI* was populated via energy transfer using anthracene, [13] as shown in Figure S20 (Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Figure 2a illustrates the absorption spectrum of representative Triad 2 along with monomeric PDI 1 control in benzonitrile. PDI 1 revealed absorption peaks at 435, 462, 492, and 535 nm, typical of monomeric PDI compounds [15] . Interestingly, Triad 2 revealed two broad peaks centered around 447 and 639 nm.…”
Section: Resultsmentioning
confidence: 98%
“…It is worth highlighting two different SiPc compounds, asymmetrically and axially functionalized with both perylenediimide (PDI) and fulleropyrrolidine electroactive units, recently published by our research groups . Analyzing both works together, we concluded that, to efficiently obtain long‐lived charged separated states, it is preferable to have only fullerene‐C 60 subunits in the axial positions of an electron‐rich SiPc moiety, wherein the distance should be fixed through adequate‐length rigid connectors.…”
Section: Introductionmentioning
confidence: 89%
“…It is worth highlighting two different SiPc compounds, asymmetrically and axially functionalized with both perylenediimide (PDI) and fulleropyrrolidine electroactive units, recently published by our research groups. [51,52] Analyzing both works together, we concluded that, to efficiently obtain long-lived charged separated states, it is preferable to have only fullerene-C 60 subunits in the axial positions of an electron-rich SiPc moiety, wherein the distance should be fixed through adequate-length rigid connectors. Here, we present the synthesis, characterization and evaluation of their photophysical properties of a series of triads (C 60 -SiPc-C 60 1 and 2) where a SiPc unit, specially designed to present an improved electron donating character, with eight 2,6-dimethylphenoxyl groups arranged in the peripheral positions, is combined, in a covalent manner, with two fullerene-C 60 appends.…”
Section: Introductionmentioning
confidence: 99%